The decisiën of Pieter Ockers (1628-1678) - Sirks, A (2003)
Pieter Ockers (1628-1678), who was a member of first the Court and then the Supreme Court of Holland, Zeeland and Westfriesland, left at his death two collections of writings. One consists of again three selections: of decisions of the Court in the period 1656-1669, of decisions of the Supreme Court in the period 1669-1678, and reworked Latin versions of decisions of the second selection. It has been uncertain whether he was the author of these selections, but it is now established by the fact, that, first, he assisted at all here recorded sessions of the Supreme Court still traceable in the archives and, secondly, that he was the only councillor to have assisted at all these traced sessions. This manusceript is now available in an edition by H.C. Gall and, though not impeccable, makes the texts well accessible. Particularly the deciphered references to literature, which Ockers added, are a boon. The other collection, an autograph, consists of 22 exercises in Roman Law, mainly in the law of inheritance, apparently meant to keep himself sharp.